EFFECT OF SPRAYING WITH BEETROOT EXTRACT AND POTASSIUM SULFATE ON SOME VEGETATIVE, CHEMICAL, AND FRUIT CHARACTERISTICS OF STRAWBERRY PLANT, VARIETY RUBY GEM - H. H. Al-Omrani; R. M. Hamad; N. T. Abd (مجلة الأنبار للعلوم الزراعية)
The experiment was carried out in one of private nurseries in Diwaniyah Governorate, Iraq, for 2022 agricultural season to study the effect of spraying with beetroot root extract in concentrations (0, 10, 20 ml l-1), potassium sulfate in concentrations (0, 1.5, 3 gm l-1) and the interaction between them on some vegetative, chemical and fruit Quality of strawberry plant., Factorial experiment was conducted according to randomized complete block design(RCBD) with three triplicates and compared between treatments by using the least significant differences(LSD) at 0.05 level. Interaction between treatments were also statistically significant; however, the B2K2 treatment yielded the most significant increases in leaf area, relative chlorophyll, Concentration of nitrogen in leaf nitrogen, phosphorus, potassium, iron, fruit size and weight, substance dry matter percentage and The total soluble solids in fruits amounted to 17.15%, 80.48 cm2 leaf-1, 63.30 SPAD unit, 2.19%, 0.232%, 1.74%, 198.00 mg kg-1, 34.28 gm fruit-1, 49.61 cm3, 13.94%, respectively